GLACIOLOGICAL RESEARCH PROGRAM IN EAST QUEEN MAUD LAND, EAST ANTARCTICA PART 8,1986-1987 - NISHIO, Fumihiko; OHMAE, Hirokazu (National Institute of Polar Research, 1989)
P(論文) departmental bulletin paper